Study of Socio-economic and Psychological Characteristics of Farmers towards Climate Change - Meghwal, Pankaj Kumar; Singh, Rajkumar Josmee; B., Muthu Lakshmi; Lego, Inne; Devi, Konjengbam Monika (International Journal of Bio-resource and Stress Management, 2017)
A study was carried out to study the socio-economic and psychological profile of Climate Change Vulnerable Farmers in agriculture. The state of Madhya Pradesh (MP) has reasons to be concerned about climate change, as the state has a large population dependent on agriculture and forests for livelihood and its economy is also dependent on agriculture and natural resources and any adverse impact on these and allied sectors will negate the efforts to alleviate poverty and ensure sustainable livelihood for the population. Keeping in view the above specifications the following research objective was framed viz. To study personal, socio-economic and psychological characteristics of farmers. The study followed exploratory research design. Mixed-method sampling procedure was followed. The study had been conducted at Manasa block of Neemuch district and Malhargarh block of Mandsaur district of Madhya Pradesh. Two villages were selected purposively from each of the selected blocks thereby constituting four villages for the study. A total of 60 farmers were selected by way of proportionate random sampling method. The data collected were processed and analysed using statistical tools such as frequency, percentage, mean and standard deviation. With regards to ‘Decision-Making on Adoption of Mitigation and Adaptation Practices of Climate Change Practices in Agriculture,’ it was revealed that majority of the respondents i.e. 70.00% belonged to category of high level of Decision-making followed by 18.33% and 11.66% who belonged to categories of medium and low level of Decision-Making on adoption of mitigation and adaptation practices of climate change practices in agriculture respectively.